Acute Limbic Encephalitis in Japanese Children - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2010)
Clinical, laboratory, and radiographic findings in 14 cases (median age 10 years; range 4-14 yrs) of nonparaneoplastic limbic encephalitis were analyzed by researchers at the National Center of Neurology and Psychiatry, Kodaira, Japan.